Pulmonary rehabilitation for mild chronic obstructive pulmonary disease: a systematic review - Jácome, Cristina (2018)
BACKGROUND: Pulmonary rehabilitation (PR) is effective in improving exercise capacity and health-related quality of life (HRQOL) in patients with moderate-to-very-severe COPD. Quadriceps strength and HRQOL can be impaired in patients with mild COPD, therefore, patients at this grade may already benefit from PR. However, the impact of PR in patients with mild COPD remains unestablished. Thus, this systematic review assessed the impact of PR on exercise capacity, HRQOL, health-care resource use and lung function in patients with mild COPD. METHODS: The Web of Knowledge, EBSCO, MEDLINE, and SCOPUS databases were searched up to April 2013. Reviewers independently selected studies according to the eligibility criteria. RESULTS: Three studies with different designs (retrospective, one group pretest-posttest, and randomized controlled trial) were included. Out-patient PR programs were implemented in two studies, which included mainly aerobic, strength, and respiratory muscle training. The randomized controlled trial compared a PR home-based program, consisting of 6 months of walking and participating in ball games, with standard medical treatment. Significant improvements in exercise capacity (effect size [ES] 0.87–1.82) and HRQOL (ES 0.24–0.86) were found when comparing pretest-posttest data and when comparing PR with standard medical treatment. In one study, a significant decrease in hospitalization days was found (ES 0.38). No significant effects were observed on the number of emergency department visits (ES 0.32), number of hospitalizations (ES 0.219), or lung function (ES 0.198). CONCLUSIONS: Most of the PR programs had significant positive effects on exercise capacity and HRQOL in patients with mild COPD; however, their effects on health-care resource use and lung function were inconclusive. This systematic review suggests that patients with mild COPD may benefit from PR; however, insufficient evidence is still available. Studies with robust designs and with longer follow-up times should be conducted.